ChemInform Abstract: Imidazolium and Benzimidazolium Salts: A Veritable Playground for Organic and Supramolecular Chemists. Issue 9 (February 2016) - Gauchot, Vincent; Gravel, Julien; Vidal, Marc; Charbonneau, Mathieu; Kairouz, Vanessa; Schmitzer, Andreea R.
Abstract: Review: [35 refs.